Edukasi Keterampilan Manajerial bagi pelaku UMKM - Fatwara, Medy Desma; Rakhman, Abdulah; Dewi, Dyah Utami; Sari, Nova Permata (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting community economic development; however, many business actors still face limitations in managerial skills, particularly in business planning, financial management, marketing strategies, and customer service. Therefore, this community service program aimed to strengthen managerial skills among community members in the Srengseng Sawah area, Jagakarsa, South Jakarta. The participants consisted of university students, MSME actors, online sellers, and housewives who run side businesses. The program was implemented through educational training, interactive discussions, case studies, and practical simulations focusing on basic management functions such as planning, organizing, actuating, and controlling. Evaluation was conducted using observation, questionnaires, and simple pre-test and post-test assessments to measure participants’ understanding before and after the activity. The results of the program showed a significant improvement in participants’ knowledge and skills in managing their businesses, particularly in financial recording, business planning, customer service, and digital marketing practices. Overall, the program contributed to enhancing participants’ managerial capacity and supporting the sustainability and competitiveness of small businesses in the local community